Perbedaan Kemampuan Berpikir Kreatif Siswa Kelas ViiiSemester Ii Smp Muhammadiyah 4 Sambi Boyolali Tahun Ajaran 2015/2016 Menggunakan Model Pembelajaran Problem Solving Dan Creative Problem Solving - Eka Rahmawati, Arin; , Dr. Siti Chalimah, M.Pd (2016)
The ability to think creatively is the basic capital that must be owned by the students so that later students can solve problems that will be encountered in real life. This research is aimed to determine differences the students ability of creative thinking in eighth grade students of SMP Muhammadiyah 4 Sambi Boyolali academic year 2015/2016 by using model Problem Solving and Creative Problem Solving toward. The mothod used was Quasy Experiment design with pretest and posttest design. The sample of this research are Problem Solving experiment class (VIII B) and Creative Problem Solving experiment class (VIII A). Data analysis using parametric test it is Independent Sample t Test by using SPSS version 15. Based on the test by using Independent Sample t Test α=5% it can be found significant value 0,682 > 0,05 so that there is no significant differences. The result of analysis N-Gain shows that the improvement the students ability of creative thingking Creative Problem Solving class is higer than Problem Solving class. CPS class gets 0,38 it is categorized as sufficient, PS class got 0,34 it is categorized as sufficient. Based on the result analysis, it can be conclude that there is no significant differences between Problem Solving model with Creative Problem Solving toward the students ability to be creative thingking in eighth grade students of SMP Muhammadiyah 4 Sambi academic year 2015/2016. The enhancement of student's creative thingking Creative Problem Solving model is higer than Problem Solving.